Manajemen Hubungan Sekolah dan Orang Tua Dalam Meningkatkan Perkembangan Anak di Taman Kanak-Kanak: Sebuah Systematic Literature Review - Tika Suri (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the management of the relationship between schools and parents in enhancing child development in kindergarten through a systematic literature review approach. Effective management of the relationship between schools and parents is expected to strengthen the educational process and support children's holistic development, including cognitive, social, emotional, and physical aspects. In this study, the author collects and analyzes various literatures related to the role of parents in early childhood education, communication strategies implemented, and the impact of collaboration between schools and parents on child development. The results of the literature review indicate that parental involvement in children's education can increase learning motivation, build self-confidence, and facilitate social development in school. Additionally, open communication and emotional support provided by parents play a significant role in child development in kindergarten. This study also finds that good management by schools in building positive relationships with parents can create a more inclusive learning environment and support children's growth. Therefore, it is important for schools to develop effective communication strategies and empower parents in the early childhood education process.